Healthcare expenditure on Indigenous and non-Indigenous Australians at high risk of cardiovascular disease - Blake Angell; Tracey-Lea Laba; Tom Lung; Alex Brown; Sandra Eades; Tim Usherwood; David Peiris; Laurent Billot; Graham Hillis; Ruth Webster; Andrew Tonkin; Christopher Reid; et al. (BMC, 2017)
Abstract Background In spite of bearing a heavier burden of death, disease and disability, there is mixed evidence as to whether Indigenous Australians utilise more or less healthcare services than other Australians given their elevated risk level. This study analyses the Medicare expenditure and its predictors in a cohort of Indigenous and non-Indigenous Australians at high risk of cardiovascular disease. Methods The healthcare expenditure of participants of the Kanyini Guidelines Adherence with the Polypill (GAP) pragmatic randomised controlled trial was modelled using linear regression methods. 535 adult (48% Indigenous) participants at high risk of cardiovascular disease (CVD) were recruited through 33 primary healthcare services (including 12 Aboriginal Medical Services) across Australia. Results There was no significant difference in the expenditure of Indigenous and non-Indigenous participants in non-remote areas following adjustment for individual characteristics. Indigenous individuals living in remote areas had lower MBS expenditure ($932 per year P < 0.001) than other individuals. MBS expenditure was found to increase with being aged over 65 years ($128, p = 0.013), being female ($472, p = 0.003), lower baseline reported quality of life ($102 per 0.1 decrement of utility p = 0.004) and a history of diabetes ($324, p = 0.001), gout ($631, p = 0.022), chronic obstructive pulmonary disease ($469, p = 0.019) and established CVD whether receiving guideline-recommended treatment prior to the trial ($452, p = 0.005) or not ($483, p = 0.04). When controlling for all other characteristics, morbidly obese patients had lower MBS expenditure than other individuals (−$887, p = 0.002). Conclusion The findings suggest that for the majority of participants, once individuals are engaged with a primary care provider, factors other than whether they are Indigenous determine the level of Medicare expenditure for each person. Trial registration Australian New Zealand Clinical Trials Registry ACTRN 126080005833347.